RANCANG BANGUN SISTEM INFORMASI POINT OF SALES BERBASIS WEB PADA JDC RESTO - Khairul Huda; Hargokendar Suhud; Youfih Herlina (Journal of Informatics and Computing (RANDOM), 2023)
JDC restaurant is a business engaged in the catering sector which provides a form of service for ordering food and drinks both on a large and small scale. The sales system currently used is still manual, this makes the sales transaction process and reporting ineffective and inefficient. This manual process makes the data presented less accurate and has a high risk of errors, damage, and data loss. Based on these problems, it is necessary to have a web based point of sales system where all business processes are computerized so that it is expected to support performance, facilitate and optimize business processes at JDC restaurants. System testing is carried out using black box testing indicating that the system has succeeded in carrying out input, processing, and producing output as expected in the system design.